2013
DOI: 10.1088/0268-1242/28/12/125006
|View full text |Cite
|
Sign up to set email alerts
|

Study of transport properties of copper/zinc-oxide-nanorods-based Schottky diode fabricated on textile fabric

Abstract: In this work, a copper/zinc-oxide (ZnO)-nanorods-based Schottky diode was fabricated on the textile fabric substrate. ZnO nanorods were grown on a silver-coated textile fabric substrate by using the hydrothermal route. Scanning electron microscopy and x-ray diffraction techniques were used for the structural study. The electrical characterization of copper/ZnO-nanorodsbased Schottky diodes was investigated by using a semiconductor parameter analyzer and an impedance spectrometer. The current density-voltage (J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 27 publications
4
20
0
Order By: Relevance
“…All the existing peaks in the XRD spectrum are designated to the specific crystal planes such as (100), (002), (101), (102), (110), (103), (200), (112), and (201) are associated with the hexagonal wurtzite structure of ZnO NWs. 29,31 One additional peak associated to CNTs is present in the graph. Another XRD spectrum (black) is showing the diffraction peaks associated with the hexagonal wurtzite structure of ZnO along with two additional peaks associated with silver (Ag).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All the existing peaks in the XRD spectrum are designated to the specific crystal planes such as (100), (002), (101), (102), (110), (103), (200), (112), and (201) are associated with the hexagonal wurtzite structure of ZnO NWs. 29,31 One additional peak associated to CNTs is present in the graph. Another XRD spectrum (black) is showing the diffraction peaks associated with the hexagonal wurtzite structure of ZnO along with two additional peaks associated with silver (Ag).…”
Section: Resultsmentioning
confidence: 99%
“…32 Similarly, in all curves the most intense peak was the (002) indicated that the growth orientation is along the c-axis. [27][28][29]31 A piezoelectric potential is generated when the ZnO NWs are bent by the AFM tip and the mechanical energy from this action induces an electric field along the direction of applied force due to the lattice deformation in the NWs. The mechanical energy is then transformed into electrical energy when the AFM tip and the NWs are in forward bias.…”
Section: Resultsmentioning
confidence: 99%
“…The fabric was cleaned by ultrasonic bath in isopropanol, acetone and deionized water, and then dried with nitrogen air pressure. The most common low temperature, environment friendly, economic and simple ACG method was used for the growth of ZnO NWs, as reported in our previously published articles . Ammonia solution 25% was added for controlling the diameter of grown ZnO NWs and increasing the growth rate .…”
Section: Methodsmentioning
confidence: 99%
“…Ammonia solution 25% was added for controlling the diameter of grown ZnO NWs and increasing the growth rate . Prior to the growth of ZnO NWs, a seed solution containing ZnO nanoparticle was prepared by dissolving zinc acetate in methanol and was deposited on the textile substrate by spin coating at a speed of 4000 rpm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation